Syndromes : (McGraw-Hill Medical Publishing Division, 2006)
Essential medical facts on over 2,000 genetic syndromes. Organized alphabetically, this book provides comprehensive medical coverage for each syndrome, from genetic basis to manifestations to related medical considerations. Features anesthetic considerations for each syndrome as well as 180 illustrations and an easily accessible standardized, two-column format.